If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -9) = -2(x + -41) Reorder the terms: 8(-9 + x) = -2(x + -41) (-9 * 8 + x * 8) = -2(x + -41) (-72 + 8x) = -2(x + -41) Reorder the terms: -72 + 8x = -2(-41 + x) -72 + 8x = (-41 * -2 + x * -2) -72 + 8x = (82 + -2x) Solving -72 + 8x = 82 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -72 + 8x + 2x = 82 + -2x + 2x Combine like terms: 8x + 2x = 10x -72 + 10x = 82 + -2x + 2x Combine like terms: -2x + 2x = 0 -72 + 10x = 82 + 0 -72 + 10x = 82 Add '72' to each side of the equation. -72 + 72 + 10x = 82 + 72 Combine like terms: -72 + 72 = 0 0 + 10x = 82 + 72 10x = 82 + 72 Combine like terms: 82 + 72 = 154 10x = 154 Divide each side by '10'. x = 15.4 Simplifying x = 15.4
| -6(x-6)=3(x-9) | | x=-55+5x | | 6(2/3)-2= | | g(-4)=2x-3x | | 8m+6n+2m-1n=0 | | 4(x-5)/-2= | | A-43/8=21/2 | | 12-5x=10-3x | | 4q-7=13 | | 2k^2-15k+84=0 | | 30ap/45ap^2 | | (-1/6x^5)*(-1/5x)= | | 2(2n+1)=7(4n+3)+4 | | 5y+4(y-7)=3(y+2)-3 | | y=4+ln(x-1) | | 5(a-4)=3a+14 | | 2(5x-3)-2x+7= | | -5(3t-2)+7t=4t-9 | | 3x-7+6x+2= | | -5(3t-2)+4t=8t-6 | | -14+n=-11 | | 2X^2+19x+80=0 | | 54=-3/4p | | 9x+y=-26 | | f(0)=(2x^(2)-10)/(7x-5) | | 1.21x=3.2 | | 3.2x=1.21 | | X+-11=-12 | | -2(a+3)-5=-4(a-2)+1 | | 3(7m+4)+5=6(5m-3)-4m | | -21+8+3x= | | 5(2c+4)+4c=8(3c-2)+6 |